Oral tongue squamous cell carcinoma survival as stratified by age and sex: A surveillance, epidemiology, and end results analysis. (21st December 2018) - Mukdad, Laith; Heineman, Thomas E.; Alonso, Jose; Badran, Karam W.; Kuan, Edward C.; St. John, Maie A.
Abstract : Objectives/Hypothesis: To utilize the Surveillance, Epidemiology, and End Results (SEER) database to elucidate differences in predictors of survival in oral tongue squamous cell carcinoma (OTSCC) as stratified by age and sex. Study Design: Retrospective, population‐based database analysis. Methods: The SEER registry was utilized to calculate survival trends for patients with OTSCC between 1973 and 2012. Patient data were then stratified by age (≤40 years vs. >40 years) and sex, then analyzed with respect to race, stage, grade, and treatment modalities. Overall survival (OS) and disease‐specific survival (DSS) were calculated and compared. Results: There were 16, 423 cases of OTSCC identified, with 526 and 706 young female and male patients, respectively. Young female patients had improved OS and DSS as compared to young male patients (75% vs. 67% at 5 years), which is better than older patients ( P < .001). Younger patients were more likely to receive surgery ( P < .001) and combination surgery and radiation ( P < .001) as compared to older patients. On multivariate analysis, tumor stage was uniformly associated with worse OS and DSS ( P < .05), with surgery predicting improved OS and DSS in all groups except young females ( P < .05). Higher tumor grade predicted worse OS and DSS in older patients, but not younger patients ( P < .05). Conclusions: OTSCC appears to present with relatively heterogeneous characteristics across different age groups and sexes. Despite the rising incidence of OTSCC in young individuals, our study demonstrates that young patients have improved survival rates compared to older patients. Level of Evidence: NA Laryngoscope, 129:2076–2081, 2019